2022
DOI: 10.3389/fpls.2022.903643
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Rice Aboveground Biomass by Combining Canopy Spectral Reflectance and Unmanned Aerial Vehicle-Based Red Green Blue Imagery Data

Abstract: Estimating the aboveground biomass (AGB) of rice using remotely sensed data is critical for reflecting growth status, predicting grain yield, and indicating carbon stocks in agroecosystems. A combination of multisource remotely sensed data has great potential for providing complementary datasets, improving estimation accuracy, and strengthening precision agricultural insights. Here, we explored the potential to estimate rice AGB by using a combination of spectral vegetation indices and wavelet features (spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…The visible light color channel contains li etation information. However, many previous studies have shown that some com rial operation of different color channels [14][15][16] can better reflect vegetation infor Therefore, in this paper, 25 commonly used visible light vegetation indexes and channels were selected to form 28 vegetation index variables. The selected vegeta dex variables are shown in Table 5.…”
Section: Segmentation In Single Tree Scale and Classification Of Domi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The visible light color channel contains li etation information. However, many previous studies have shown that some com rial operation of different color channels [14][15][16] can better reflect vegetation infor Therefore, in this paper, 25 commonly used visible light vegetation indexes and channels were selected to form 28 vegetation index variables. The selected vegeta dex variables are shown in Table 5.…”
Section: Segmentation In Single Tree Scale and Classification Of Domi...mentioning
confidence: 99%
“…Vegetation spectral information, such as the vegetation index and image texture, can fully express leaf color, vegetation richness, and health status [11,12]. In recent years, some studies have applied the visible light spectrum [13], image texture [14,15], and visible vegetation index [16][17][18] to estimate vegetation biomass by using the practical and inexpensive measurement of UAVs equipped with cameras. Both Wang Li et al (2016) [19] and Bo Li et al (2020) [20] have used vegetation index (VI) features and vegetation heightrelated variables obtained using aerial photography to estimate aboveground biomass and forecast the yield of maize and potato, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…As a new near-ground remote sensing approach, unmanned aerial vehicles (UAVs) ( de Castro et al., 2021 ) can flexibly provide higher-resolution and bigger-scale images by carrying different sensors (e.g., multispectral, hyperspectral, and thermal infrared cameras). It has already been widely used in the inversion of physiological and biochemical parameters such as plant height (PH) ( Che et al., 2020 ), leaf area index (LAI) ( Chen et al., 2022b ), nutrient states ( Xu et al., 2021 ), and aboveground biomass ( Wang et al., 2022 ). Equipped with hyperspectral imaging (HSI) sensors, Liu and Peng.…”
Section: Introductionmentioning
confidence: 99%
“…The vegetation functional datasets include FPAR, canopy chlorophyll content, and ecosystem functional characteristics such as carbon storage and evapotranspiration. At present, some common methods have been used to estimate biomass [4,[37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%